ANALYTICAL STUDIES ON VOLUME DETERMINATION OF LEG ULCER USING REVERSE ENGINEERING METHOD - KIONG, CHONG KIAN (2013)
Reverse Engineering is defined as the process of obtaining a geometric CAD model by digitizing the existing objects. In medical application, it is applied to obtain the CAD model of human skin surface. Chronic leg ulcer refers to the wound which does not heal in the predictable period. Approximately 1% of the world population will develop leg ulcers in their lifespan.